The Influence of Motivation, Work Ethic and Work Discipline on the Performance of Employees in the Public Works and Spatial Planning Department of Gunungsitoli City - Noverman Lase (CV Edujavare Publishing, 2025)
Employee performance is one of the most important elements in achieving organizational goals, especially within government institutions that directly provide services to the public. This study aims to analyze the influence of motivation, work ethic, and work discipline on employee performance at the Public Works and Spatial Planning Office of Gunungsitoli City. This research employed a quantitative approach using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 3 software for data analysis. The population of this study consisted of employees at the Public Works and Spatial Planning Office of Gunungsitoli City, with 70 respondents selected as the research sample. Data were collected through questionnaires, observations, and documentation studies. The results of the study revealed that motivation has a positive and significant effect on employee performance, with a path coefficient value of 0.285, a t-statistic of 2.536, and a p-value of 0.012. Work ethic also demonstrated a positive and significant influence on employee performance, with a path coefficient value of 0.331, a t-statistic of 2.786, and a p-value of 0.006. Furthermore, work discipline showed the strongest influence on employee performance, with a path coefficient value of 0.344, a t-statistic of 3.147, and a p-value of 0.002. Simultaneously, motivation, work ethic, and work discipline explained 70.5% of the variance in employee performance, as indicated by the R-square value of 0.705. The findings indicate that improving employee motivation, strengthening work ethic, and enforcing work discipline are essential strategies for enhancing employee performance and organizational effectiveness within public sector institutions.